(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the features of independent thinking in preschool children, focusing on their ability to make decisions, solve problems, and express original ideas. Through a comprehensive literature review and empirical study, the research identifies key characteristics such as curiosity, creativity, and self-initiated problem-solving. The study employs observational and interview methods to gather data from preschool settings. Results highlight the developmental stages of independent thinking and environmental factors that foster it. The discussion addresses implications for early childhood education, with suggestions for nurturing independent thinking in young learners.